﻿Protelenomus Kieffer is a derived lineage of Trissolcus Ashmead (Hymenoptera, Scelionidae), with comments on the evolution of phoresy in Scelionidae - Cheng-Jin Yan; Elijah Talamas; Zachary Lahey; Hua-Yan Chen (Journal of Hymenoptera Research, 2022)
Species of the genus Protelenomus Kieffer (Platygastroidea, Scelionidae) are phoretic egg parasitoids of coreid bugs. The discovery, DNA sequencing, and molecular phylogenetic analysis of a Protelenomus species phoretic on Cletus punctiger (Dallas) (Hemiptera, Coreidae) shows that Protelenomus is a derived lineage of Trissolcus Ashmead. Protelenomus is treated as a junior synonym and a new species of phoretic Trissolcus, T. siliangae Yan, Chen & Talamas, is described from China.